2016
DOI: 10.3168/jds.2015-10812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk replacer feeding rate and functional fatty acids on dairy calf performance and digestion of nutrients

Abstract: Calves fed large amounts of milk replacer (MR) gain more body weight preweaning than calves fed less MR; however, postweaning growth may be reduced because of impaired digestion of nutrients. This was explored in the current research, as was the inclusion of functional fatty acids (NT) that could ameliorate some poor growth and digestion issues in calves fed large amounts of MR. Two MR rates [moderate (MOD) or aggressive (AGG)] with and without NT were compared using 48 male Holstein calves initially 3d old (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
74
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 37 publications
16
74
4
Order By: Relevance
“…Starter fed in the current study and the previous digestibility studies (Hill et al, 2010(Hill et al, , 2016bChapman et al, 2016) was low in fiber and high in starch. Calves fed higher-fiber starters with high amounts of MR or milk might report larger amounts of BW gain during or immediately after weaning resulting from growth of gut tissue and accumulation of gut fill from poor digestion of starter rather than muscle or bone growth.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Starter fed in the current study and the previous digestibility studies (Hill et al, 2010(Hill et al, , 2016bChapman et al, 2016) was low in fiber and high in starch. Calves fed higher-fiber starters with high amounts of MR or milk might report larger amounts of BW gain during or immediately after weaning resulting from growth of gut tissue and accumulation of gut fill from poor digestion of starter rather than muscle or bone growth.…”
Section: Discussionsupporting
confidence: 54%
“…By wk 3 of the study, ADG did not differ among treatments (Figure 2), although calves on HI and HIMOD were fed significantly more MR than MOD calves. Hill et al (2016b) reported that digestibility of NDF and ADF from a high corn and oats starter (high in starch) increased from 3 to 8 wk of age (calves weaned at 7 wk of age), likely reflecting increasing maturation of the digestive system. In their data, the digestion of ADF and NDF was lower in calves fed HI versus MOD (~0.7 kg/d of DMI), reflecting slower maturation of the digestive system in calves more than about 0.7 kg/d of MR. Lower digestibility of starter could result in greater amounts of gut fill and gut tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementing short-chain fatty acids such as butyrate can improve GIT development and calf performance. 61 Furthermore, the effect may be more pronounced in milk replacer diets in which the primary fat source is not milk fat. Milk fat already contains a significant quantity of butyrate; however, the exact concentrations of these short-chain fatty acids to supplement in milk replacer are not known.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…Milk fat already contains a significant quantity of butyrate; however, the exact concentrations of these short-chain fatty acids to supplement in milk replacer are not known. 59,61 Supplementing omega-3 PUFAs and altering the omega-6 to omega-3 PUFA ratio to transition and early lactating cows was investigated as a strategy to improve health and production performance. Feeding whole flaxseed as a source of the omega-3 PUFA, specifically a-linolenic acid, from calving until 105 days in milk (DIM) decreased the serum concentrations of the proinflammatory eicosanoid, prostaglandin E 2 .…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%